Descemet Membrane Endothelial Keratoplasty in Irreversible Corneal Edema Due to Herpes Simplex Virus Endotheliitis. Issue 1 (January 2020) - Basak, Samar K.; Basak, Soham
Abstract : Purpose: To report the clinical outcome and postoperative course of Descemet membrane endothelial keratoplasty (DMEK) in irreversible corneal edema due to herpes simplex virus (HSV) endotheliitis. Methods: This is a retrospective, noncomparative, interventional case series. Nineteen eyes of 19 patients underwent standard DMEK combined with cataract surgery (triple DMEK) between May 2016 and April 2018. All patients received perioperative oral acyclovir (ACV) and prednisolone. Patients were followed up on day 1, on day 7, at 1 month, and then at 3 monthly intervals. Preoperative and postoperative best spectacle-corrected visual acuity (BSCVA), graft clarity, pachymetry, and endothelial cell loss after 1 year were recorded. Postoperative complications and HSV recurrence were noted until the last follow-up visit. Results: All eyes were phakic with variable grades of cataract with a preoperative BSCVA of 1.0 logarithm of the minimum angle of resolution or worse. The mean follow-up period was 19.3 ± 5.4 months. After 1 year, 14 (73.7%) eyes achieved a BSCVA of 0.3 or better. Seventeen (89.5%) patients had a clear graft at the last visit without any rejection episode. One graft failed after 16 months. After 3 months, the mean pachymetry reduced from 667.1 ± 62.1 to 512.8 ± 27.1 μm ( P < 0.001). The mean endothelial cell loss after 1 year was 36.7 ± 13.4%. Three (15.8%) eyes had recurrence: one with recurrent endotheliitis and 2 with dendritic keratitis despite oral ACV, which responded to oral valacyclovir and ACV eye ointment. One patient had re-recurrence of endotheliitis after 20 months. Conclusions: DMEK in persistent corneal edema after HSV endotheliitis remains challenging but has encouraging outcomes. The postoperative course may be complicated by HSV recurrence. Prophylactic oral antivirals for 1 year or more and topical antivirals are useful for the prevention of recurrence.